Analysis of the Cause of Clearance Deviation of Planetary Gear Pair in Wind Turbine Gearbox - Yutian Zeng; Junwei Zou; Jinku Li; Jingyuan Xiao; Meiling Zhu (Jixie chuandong)
As wind power transmission gear key parts， because of irregular under strong wind and Martin shock loads， so that its work reliability decides the reliability of the wind turbine gearbox. As one of the four requirements of gear transmission， an appropriate gear clearance is a necessary condition for the normal operation of the gear pair， which is the key to reduce the impact， noise， air distance error and improve the service life of the wind turbine gearbox. For the error of the gear pair clearance in planetary gear which is the first planet transmission structure forms of wind power gearbox， through analysis on the planetary gear pair clearance from three aspects of the impact， parts manufacturing， assembly and measuring， the influence of the assembly process of the planetary gear pair clearance is confirmed， through choosing the middle-box and the main bearings， the problem of the planet wheel gear deviation is solved.